SPECTROPHOTOMETRIC QUANTITATIVE ESTIMATION AND VALIDATION OF NIMESULIDE AND DROTAVERINE HYDROCHLORIDE IN TABLET DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Three simple, sensitive and accurate UV spectrophotometric methods, I; first order derivative spectrophotometric, II; area under curve and III; multi-component method, has been developed for the estimation of drotaverine hydrochloride and nimesulide in tablets dosage form. Beers’ law was obeyed in the concentration range 5-35 µgml-1 and 10-50 µgml-1 for drotaverine (λmax = 230.5 nm) and nimesulide (λmax = 331.5 nm) respectively in methanol. All the three methods allowed rapid analysis of binary pharmaceutical formulation with accuracy. Results of analysis for three methods were tested and validated for various parameters according to ICH guidelines.